Image authentication algorithm based on trisected image basic blocks - Li, Xiang-Yang (Ji suan ji ying yong yan jiu, 2014)
As the existing block-wise lossless image authentication algorithms will sacrifice the precision of locating distortions, this paper proposed the lossless image authentication algorithm based on trisected image basic blocks. The algorithm trisected the original image recursively and connected all the basic blocks into a link. An authentication block was made up of several basic blocks. When the watermark couldn't be embedded into the authentication block, the algorithm tried to merge only one basic block from the link into current authentication block. As a result, it expanded each authentication block's size at a minimum level. Moreover, in order to prevent vector quantization attack, it took a digital signature algorithm and repeatedly embedded the signature into the authentication block via a lossless watermarking algorithm. The experimental results demonstrate that the algorithm is more accuracy than the algorithm based on adaptive combinations of image basic blocks.